Crescimento e desenvolvimento de recém-nascidos pré-termo com muito baixo peso no primeiro ano de vida - Tatiana Barcelos Pontes (2006)
The objective of this study was to describe the evolution of weight and head circumference (HC) from birth to 12 months of corrected age in very low birth weight (VLBW) preterm infants and to evaluate a possible association of these factors with the neurodevelopment outcome of the infants. Infants (n = 251) were selected from the Ambulatório da Criança de Risco/ ACRIARs longitudinal study. Data were extracted from ACRIARs records and databank. The VLBW were classified as SGA and AGA.The growth curves of weight and HC mean values were adjusted by the Count model. The analysis of the neurodevelopment outcome was performed using the Denver II Developmental Screening Test. Curves were plotted against the models proposed by Xavier (1995) and NCHS (2000). Our results showed that in terms of weight curves, neither the SGA nor the AGA presented evident cacth-up growth during the 12 months of corrected age. The HC mean curve of the AGA VLBW infants followed Xaviers and NCHSs means and 50th percentiles. The SGAVLBW infants presented HC cacth-up growth between the 7th and 8th months of corrected age. The HC growth below the 5th percentil or a z score lower than 2 at 12 months of corrected age showed significant association with abnormal outcome in the neurodevelopment test (p= 0,0008), suggesting a delay in development, as it was evidenced by other studies. Only the AGA VLBW with weight catch-down presented a significant abnormal neurodevelopment outcome (p= 0,01). Further studies at later ages are needed in order to confirm these results.